Financial Globalization : The Impact on Trade, Policy, Labor, and Capital Flows. - International Monetary Fund.; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
Assiduously tracking the trends and consequences of globalization, the IMF's quarterly magazine Finance & Development has been a major forum for discussing-and dissecting-the policy options and challenges faced by governments in an era when many national decisions transcend borders. This valuable compilation of articles published over the past eight years focuses on financial globalization, including the policy implications of the huge growth in cross-border capital flows. Articles also look at the expansion of world trade, explore the impact of globalization on jobs, taxation, and the poor, and examine the digital divide between developed and some developing countries. An extraordinary summary that distills nearly a decade of accelerated change.
How to help developing countries integrate into the global trading systemMaking Globalization Work for the Poor; Point-Counterpoint between Kevin Watkins and David Dollar and Aart Kraay; Demystifying Outsourcing; The numbers do not support the hype over job losses
English
"April 2007."
Includes bibliographical references.
Description based on print version record.
Keywords: International finance; Economic assistance -- Developing countries; Globalization; Exports and Imports; Finance: General; Macroeconomics; Globalization; Social Services and Welfare; General Financial Markets: General (includes Measurement and Data); Current Account Adjustment; Short-term Capital Movements; International Investment; Long-term Capital Movements; Government Policy; Provision and Effects of Welfare Program; Aggregate Factor Income Distribution; International economics; Finance; Social welfare & social services; Capital flows; Emerging and frontier financial markets; Capital account liberalization; Income inequality; Balance of payments; Financial markets; National accounts; Poverty; Capital movements; Financial services industry; Income distribution; United States